Anilinonaphthalene sulfonate and its magnesium and sodium salts as fluorescent protein stains - C. R. Fisher (Fungal Genetics Reports, 1969)
Anilinonaphthalene sulfonate and its magnesium and sodium salts as fluorescent protein stains